The sociological concept of the phenomenon of self-preserving behavior - Svetlana V. Funikova, Nataliya A. Mamatova, Inna S. Shapovalova, Svetlana A. Vangorodskaya, Oksana V. Shevchenko, (Opción, 2019)
The paper outlines and updates research tasks related to defining vector trends and key risks of existing self-preserving behavior models of the population at a national security scale via a mass survey, with quota sampling, distribution by gender, age and area of residence. As a result, all recommendations on the formation of appropriate health-saving behavior models are reduced to increase the personal responsibility of an individual for his/her health. In conclusion, self-preserving behavior is a system of actions and relationships aimed at preserving health during the full life cycle.